Microwave-Assisted Knoevenagel-Doebner Reaction: An Efficient Method for Naturally Occurring Phenolic Acids Synthesis - Mouterde, Louis M. M.; Allais, Florent (Frontiers in Chemistry, 2018)
The common chemical method to synthesize Phenolic Acids (PAs) involves a relatively considerable energy intake. In order to solve this issue, microwave-assisted Knoevenagel-Doebner condensations were developped. Nevertheless, these synthetic procedures prove difficult to reproduce. Herein, we developed and optimized - by using a combination of a Design of Experiment and a standard optimiztion approach - a reliable procedure that converts naturally occuring p-hydroxybenzaldehydes into the corresponding PAs with conversions of 86-99% and in 85-97% yields.